ACT 2019 - Dulan, Steven W.; Dulan, Amy; American College Testing Program; McGraw-Hill Education (Firm); Faculty of Advantage Education (New York McGraw-Hill Education, 2018)
Planning to take the ACT? This comprehensive guide provides a specific, proven prep program to help you do your best on the test. McGraw-Hill Education's ACT 2018 is packed with everything you need to prepare for the ACT's four achievement tests: English, reading, math, and science. You'll find simple, proven techniques to help you study more efficiently, avoid common mistakes and traps, and raise your score across the board--even on the optional writing test. A diagnostic test is also included so that you can assess your readiness. This updated, essential study guide features: 4 practice exams Comprehensive overview of the updated Essay format, including information on scoring Realistic practice questions with thorough answer explanations that reflect the new paired-passage format of the Reading Test Classroom-tested tips and strategies for mastering every question type Exercises that specifically address the concepts tested in all ACT sections Student-tested strategies that helped prepare thousands of exam takers for success A FREE customizable test planner app to help you organize your study schedule It's like having your own private tutor for your future success! -- Amazon.com.
Getting started. Understanding the ACT -- ACT diagnostic assessment. ACT diagnostic assessment test -- Strategies and review. Strategies to get your best score ; ACT English test : strategies and concept review ; ACT mathematics test : strategies and concept review ; ACT reading test : strategies and concept review ; ACT science test : strategies and concept review ; ACT writing test : strategies and review -- Four practice tests.
"5 full-length practice tests"--Cover.
106833
Keywords: ACT Assessment -- Study guides; ACT Assessment -- Examinations, questions, etc; Achievement tests -- Study guides; Universities and colleges -- United States -- Entrance examinations -- Study guides; Study guides; Examinations